2014
DOI: 10.1007/s11207-014-0598-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Flare Processes and Variety of the Fine Structure of Solar Radio Emission over a Wide Frequency Range of 30 – 7000 MHz

Abstract: Radiobursts exibiting fine structure observed over two years during the rising phase of Cycle 24 by the Chinese Solar Broadband Radio Spectrometer (SBRS/Huairou) in the range 1-7.6 GHz and the spectrograph IZMIRAN in the meter range (25 -270 MHz) are analyzed. In five events zebra structure, various fiber bursts and fast pulsations were observed. These observations have great importance for testing different theoretical models of fine structure formation, as, for example, only for explaining the zebra-structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…Its maximum emission flux at 06:58:30 UT was very strong, it exceeded the background flaring continuum intensity by several times (Figure 3 and 4). Tan et al (2014) showed that this ZP was simultaneously observed with ORSC/Ondrejov spectrograph and all details (stripe separations, brightness, duration, the arched shapes of each stripe and the spiky super structure) are strictly identical to the spectrogram obtained by SBRS/Huairou. The middle panel in Figure 4 shows moderate left-handed polarization, of 35 ± 5%.…”
Section: Radio Spectral Fine Structures and Dynamics Of Flare Processessupporting
confidence: 68%
See 3 more Smart Citations
“…Its maximum emission flux at 06:58:30 UT was very strong, it exceeded the background flaring continuum intensity by several times (Figure 3 and 4). Tan et al (2014) showed that this ZP was simultaneously observed with ORSC/Ondrejov spectrograph and all details (stripe separations, brightness, duration, the arched shapes of each stripe and the spiky super structure) are strictly identical to the spectrogram obtained by SBRS/Huairou. The middle panel in Figure 4 shows moderate left-handed polarization, of 35 ± 5%.…”
Section: Radio Spectral Fine Structures and Dynamics Of Flare Processessupporting
confidence: 68%
“…We do not have any convincing evidence that the mechanism, generated ZP, is the emission of Bernstein modes as this was proposed by Tan et al (2014) for the first strong ZP. First, an exact definition of the frequency separation between three (and sometimes four) zebra stripes is too problematic.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…It is impossible to consider the ten other ZP models in one publication; their importance requires additional analysis. A detailed description of the observational properties of the ZP and fiber bursts and their modern theoretical models are given in the literature (Chernov et al, 2015 and in two other reviews, Chernov, 2012 and 2016, which are freely accessible at http://www.izmiran.ru/~gchernov/).…”
Section: Introductionmentioning
confidence: 99%